(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Child labour persists in developing nations but also causes concern in developed countries due to its alarming prevalence. There is a significant importance to humanitarian research and the sustainability of nations. Child labour is a barrier to human capital building for sustainable development. By using a two-period utility maximisation problem of the representative working family consisting of adult members (the parents) and a child, the study analysed the impact of the local labour market and capital market on child labour incidence theoretically. Depending on the type of land ownership, market flaws in labour, land, and capital can lead to increased child labour and reduce human capital accumulation